Toward a New Paradigm of Ecosystem and Endemic Organism based on Spatial Zonation for Taka Bonerate Marine Protected Area - Agus Hartoko; I. Kumalasari; Sutrisno Anggoro (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
Most of present approach by authorities in designing for any conservation programs was mainly achieving target based on the width of area and not for the endemic organisms in each area.  The  old zonation method used was usually not based upon an ecological delineation but mostly using the island border  physically and without a rehabilitation zone.  In the conservation zone such as in Taka Bonerate marine park there could be a limited use zone based on the traditional use and not an intensive use activities.  The paper develop a new ecosystem and endemic organism based spatial scoring to built a new spatial zonation model which is specially dedicated for any conservation zone or a marine parks. Which would be used for a management plan and further action plan. A spatial based approach analysis with a reliable detail and adequate accuracy was  needed as a guide in the zonation processes for the management of coastal or marine protected area. The spatial modeling was a combination of satellite and field data analysis.  This spatial modeling analysis was also called as Cell Based Modeling based on raster/spatial data and  ‘spatial-scoring’ method with emphasized on the specific ecosystem and endemic organism valuation and weight approach. The  new paradigm on the “specific ecosystem and endemic organism based spatial-scoring for a new spatial model”  and targeted  existing knowledge for a beyond ‘the usual-goals’ for Marine Protected Area (MPA).  In this case is preserving and conserving “marine living fossils”: Nautilus pompilus for Taka Bonerate as well as for other cases of Latimeria menadoensis in north Sulawesi waters and Limulus.sp in Java and Kangean seas, should be designated as a “new concept of MPA-Plus”. Considering the important of deep sea vulnerable reef and atolls and sand-dune (‘bungin’) ecosystem for a protected reef-fishes: napoleon wrasse (Cheilinus undulatus),   and flying fish Cypsilurus.sp and others.   Key words : Endemic, spatial-scoring, MPA, Taka Bonerate